The Microbiome of Suaeda monoica and Dipterygium glaucum From Southern Corniche (Saudi Arabia) Reveals Different Recruitment Patterns of Bacteria and Archaea - Jalal, Rewaa S.; Sheikh, Hassan I.; Alotaibi, Mohammed T.; Shami, Ashwag Y.; Ashy, Ruba A.; Baeshen, Naseebh N.; Abulfaraj, Aala A.; Baz, Lina; Refai, Mohammed; Baeshen, Nabih A.; Fadhlina, Anis; Arifullah, Mohammed; et al. (Frontiers in Marine Science, 2022)
Soil and plant interact differently in response to the same stress (e.g. salinity) and recruit certain bacteria. The southern corniche (Saudi Arabia) has limited plant growth which could be due to the high temperature and salinity. The study aimed to determine the soil microbiome of selected plants and the interactions between soil and these plants. Suaeda monoica and Delphinium glaucum soil samples were collected from the crust (surface) and rhizosphere, while soil with no plant growth from the nearby area was used as control. High-throughput hypervariable V3–V4 region of the 16S rRNA gene was used to evaluate the shifts in soil microbiome due to growth of plant growth. The analysis detected up to 16% archaeal strains in S. monoica associated samples, while D. glaucum and control samples contained 100% bacterial strains. The top 10 phyla composition of the soil samples were Proteobacteria, Actinobacteria, Firmicutes, Gemmatimonadota, Bacteroidota, Halobacterota, Cyanobacteria, Cloroflexi, Planctomycetota, and Myxococcota. The V3-V4 region analysis successfully clustered the 5 samples into 3 clusters (control, D. glaucum and S. monoica) at higher-order classification but not at species level due to unidentified bacteria. The main differences between soil samples were due to halophyte S. monoica samples containing high amounts of halophilic archaea and halophilic bacteria. This showed that selected plants interacted differently with the soil. EC and KO-based analysis of functional genes and pathways showed that 5 pathways were specific to control, 11 pathways were observed only in D. glaucum samples, 12 pathways were expressed in S. monoica samples only, while 9 pathways were common in all samples. The study also detected numerous relatively novel genera in high abundance such as Aliifodinibius, Pontibacter, and Lacunisphaera. This showed that the soil in the sampling area is not well explored and novel species could be isolated from the soil samples and used for future research.